نظام النقد والتمويـل في البنك المركزي العراقـي: دراسة حالة (Journal of Accounting and Financial Studies ( JAFS ), 2011)
This research attempts to study Monetary system status and financing in the CIB through 4 sections, starting with the methodology and ending with conclusions and recommendations.             These two topics of Monetary and financing, that falls within the mandate of the CBI, are researched / studied relying on the resources and relevant literature. This research is a simple contribution, but meantime it is an honest attempt to elevate the effective role of the CBI which is considered one of the most pioneering central banks in the region.